Prevalence and Identification of Ectoparasites on Ruminant Animals Reared in Biu Local Government Borno State, Nigeria - Usman A.M; Zira D.J; Takko, F. S. , Baban; Umar A. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Ectoprasites have been noted as the main factor that reduces the animal’s production in the tropics. The aim of this study is to provide a database by determine the prevalence and identifying the species of ectoparasites on ruminant animals reared in Biu Local Government, Borno State, Nigeria. A total of 420 animals were examined which include 170 goats, 100 sheep and 150 cattle. Goats had the highest prevalence of 33% followed by cattle and sheep with 26.7% and 18% respectively. The different in prevalence rate between the species were not statistically significant. Female goat, sheep and cattle have the highest prevalence rate of 32(37.2%), 10(20%) and 26(34%) than male counterparts with 24(28.6%), 8(16%) and 14(19%) respectively. The different of prevalence rate between sexes of the animal were all statistically significant. Buratai and Tum had the highest of 20 (40%) each followed by Biu with the least of 16 (22.8%) in Goat while on sheep Tum has the highest prevalence of 7(23.3%) followed by Buratai and Biu with 5(16.7%) and 6(15%) respectively. However, on cattle Buratai has the highest prevalence of 16(33.3%) followed by Tum and Biu with 12(25%) and 12(22.2%) respectively. The different in prevalence rate in different locations in all species were statistically not significant. The result shows tick species Amblyomma variegahum has highest prevalence of 70(21.7%) followed by Boophilus annulatus, Hyalomma trancatum, Boophilus geigy, Rhipicephalis species, Hyalomma rufipes and Amblyomma splendidum with 53(16.5%), 40(12.4%), 29(9%), 27(8.4%) and 27(8.4%) and lice species Linognathus vituli, Haematopinus bovis, Solenopotes capillatus with 39(12.1%), 11(3.4%) and 9(2.5%) respectively. This investigation gives baseline information on the level and species of ectoparasites in the study area. Therefore, appropriate control measures need to be taken to reduce the prevalence rate to the minimal level and improve the health status of their animals which will maximize their profit.